EARNINGS ANNOUNCEMENTS AND COMPETING INFORMATION: THE INDONESIAN EVIDENCE - Dedhy Sulistiawan; Jogiyanto Hartono; Eduardus Tandelilin; Supriyadi Supriyadi (Journal of Indonesian Economy and Business (JIEB), 2014)
The main purpose of this study is to provide empirical evidence of the relationship between investors’ responses to two events, which are, (1) earnings anouncements, and (2) technical analysis signals, as competing information. This study is motivated by Francis, et al. (2002), whose study used stock analyst’s recommendations as competing information in the U.S stock market. To extend that idea, this study uses technical analysis signals as competing information in the Indonesian stock market. Using Indonesian data from 2007-2012, this study shows that there are price reactions on the day of a technical analysis signal’s release, which is prior to earnings announcements. It means that investors react to the emergence of competing information. Reactions on earnings announcements also produce a negative relationship with the reaction to a technical analysis signal before an earnings announcement. This study gives evidence about the importance of technical analysis as competing information to earnings announcements.